Differential impact of belatacept and cyclosporine A on central aortic blood pressure and arterial stiffness after renal transplantation. (23rd July 2014) - Seibert, Felix S.; Steltzer, Julia; Melilli, Eduardo; Grannas, Gerrit; Pagonas, Nikolaos; Bauer, Frederic; Zidek, Walter; Grinyó, Josep; Westhoff, Timm H.
Abstract Calcineurin inhibitors (CNI) are potent vasoconstrictors and induce an acceleration of arteriosclerosis, thus contributing to the cardiovascular risk after renal transplantation. The study compares the impact of belatacept and cyclosporine A (CsA) on arterial stiffness and central aortic blood pressure. We performed a case–control study in 46 patients (23 on belatacept and 23 on CsA) matched for age, body mass index, time after transplantation, and time on dialysis prior to transplantation. Pulse wave analysis (SphygmoCor, AtCor®) was used to assess central aortic blood pressure, aortic augmentation pressure, and pulse wave velocity (PWV) as a marker of arterial stiffness. Assessment of vascular function was performed after a minimum of 20 months and a median follow‐up of 81 months post‐transplant. Peripheral systolic and diastolic blood pressure did not significantly differ in the two groups (p > 0.05 each). The central aortic augmentation pressure was higher in the CsA group (12.7 mmHg vs. 7.3 mmHg, p = 0.048). PWV as a measure of arterial stiffness did not differ in the two groups. Thus, belatacept is not associated with a significant difference in arterial stiffness compared to CsA after a median of 81 months post‐transplant. It is associated, however, with a lower aortic augmentation pressure, a strong independent cardiovascular risk factor.